An introduction to radiography - Easton, Suzanne (Churchill Livingstone/Elsevier, 2009)
Provides foundation in radiography for first year degree students by giving an overview of the basic principles. This book covers the core knowledge and standards for professional practice to enable assistant practitioners to pass their NVQ examinations, practise their skills effectively and provide good patient care.